Determination of Calcium and Phosphorus Digestibility of Individual Feed Ingredients as Affected by Limestone, in the Presence and Absence of Phytase in Broilers - Kyle Marcus Venter; Roselina Angel; Jamie Fourie; Peter William Plumstead; Wenting Li; Henk Enting; Yueming Dersjant-Li; Christine Jansen van Rensburg (Animals)
To begin formulating broiler diets on a digestible calcium (Ca) basis, robust Ca digestibility values for ingredients and factors affecting this digestibility are needed. This study had three main objectives: (1) determine the standardized ileal digestibility (SID) of Ca and phosphorus (P) for seven plant-based feed ingredients in broilers, (2) assess the impact of phytate source on SID Ca from limestone (LS), and (3) evaluate the effect of phytase on SID Ca and P for the different ingredients. Two experiments were conducted to satisfy these objectives. In Experiment 1, a 4 × 2 × 2 factorial design was used, with four plant-based feed ingredients (corn, wheat, sorghum, and full-fat soybean meal (FFS)), two LS inclusions in the diet (absence of LS and the inclusion of LS required to achieve 0.65% Ca in the final diet), and two phytase doses (0 and 1000 FTU/kg diet). Experiment 2 utilized a 3 × 2 × 2 factorial design with three plant-based ingredients (soybean meal (SBM), rapeseed meal (RSM), and sunflower meal (SFM)), two LS inclusions in the diet (absence of LS and the inclusion of LS required to achieve 0.65% Ca in the final diet), and two phytase doses (0 and 1000 FTU/kg diet). The trial had eight replicate pens (6 broilers/replicate) per treatment. Data were analyzed using a factorial analysis in JMP Pro 16.0 with means separation performed when p < 0.05, using Tukey HSD. The SID Ca in the absence of phytase for wheat (72.9%) and FFS (69.9%) was higher (p < 0.05) than for sorghum (54.5%) and corn (46.3%). In Experiment 2, the SID Ca in the absence of phytase from SFM (61.0%) was higher (p < 0.01) than RSM (42.7%) and SBM (46.8%). The SID Ca from added LS was affected by the ingredient, with diets containing wheat and FFS resulting in the lowest (p < 0.05) SID Ca versus those containing corn and sorghum irrespective of phytase dose in Experiment 1, and the lowest (p < 0.05) for SBM and RSM vs. SFM in the absence of phytase in Experiment 2. Phytase supplementation increased (p < 0.01) SID Ca and SID P across all feed ingredients compared to non-supplemented diets. There was a two-way interaction (p < 0.01) of LS addition and ingredient on SID P in both experiments. The results of this study provide SID Ca and SID P values from the selected ingredients and show that phytate from different ingredients reacts differently with Ca from LS and should be considered when developing SID coefficients of Ca and P for use in commercial broiler feed formulation. The SID coefficients of Ca and P for the individual feed ingredients evaluated in this study will allow for the further development and transition towards dCa and dP in commercial feed formulation.